Visible-light-promoted hydroxysulfonylation of alkylidenecyclopropanes: synthesis of cyclopropane-containing β-hydroxysulfones. Issue 24 (1st November 2019) - Liu, Chuang; Yang, Yan-Jie; Dong, Jun-Ying; Zhou, Ming-Dong; Li, Lei; Wang, He
Abstract : Cyclopropane-containing β-hydroxysulfones and cyclopropyl styrenes have been synthesised from readily available ACPs and sulfuryl chloride via visible-light photoredox catalysis. Abstract : Visible-light-promoted hydroxysulfonylation of the C–C double bond of alkylidenecyclopropanes (ACPs) with conservation of the cyclopropyl ring has been developed. The difunctionalization reaction exhibits a broad substrate scope with excellent functional group compatibility, affording a series of cyclopropane-containing β-hydroxysulfones and cyclopropyl styrenes in 34–91% yields under mild conditions. The preliminary mechanistic investigation indicates that this difunctionalization reaction includes a radical process via a sulfone radical.